Indeks Subjek Volume 31, Tahun 2011 - Indeks Subjek Volume 31, Tahun 2011 (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2011)
Acid hydrolysis 384Activated carbon 30Adsorption 30Adsorption by active carbon 305Adsorption isotherm 30Afl atoxin B1 168Agroecotourism 139Alcohol 325Alkali 190Ana apple juice 352Analytical Hierarchy Process (AHP) 139Anthocyanidin 93Anthocyanin 93Antibacterial activity 305Antioxidant 290Antiplatelet 52Audit 1Autooxidation 281